PEMBUATAN MESIN PENGERING KELAPA MENGGUNAKAN SUMBER ENERGI TERBARUKAN UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Hendra Hendra; Yenni Suhartini; Anizar Indriani; Hernadewita Hernadewita (Universitas Bengkulu, 2018)
IbM community service aims to help villagers to make coconut drying machine. This dryer can help people in the processing a crops product with high water content quality, hygienic, short time and are not dependent on climate or weather. This machine mechanism can help the farmers in processing coconut plantations product, especially in the process of drying the crop so that sale value of dried coconut is high and incomes become increase. In the previous drying method, the coconut is drying by the open system where as the method is dependent on natural and climatic conditions. This is very detrimental to the community because of losses in terms of drying time, the water quality and higyenis product is low and other unsecured cause dry oil prices to be low. By using a drying machine the drying time is shorter, water content and quality of drying can be controlled and hygiene will also be maintained. Increased levels of water quality and hygiene product drying will make the selling price of coconut increases. Increased selling prices will impact on people's incomes so that the welfare of society for the better copra producer. In addition to the increase in people's income, it is a national issue of poverty alleviation, employment generation and application of new technology-based products in the country will be met. This community service is done at the Village Pasar Pedati and Village Harapan District of Pondok Kelapa through training how to make the dryer machine so that people can make this tool in order to increase their income as both a producer of copra with maintained quality as well and the creator of this drying machine. From the results of devotion performed shows that the people be able to make the dryer machine with a drying time of wet coconut weighing 1.4 kg to 1 kg within 7 hours, the water content of 40% decreased to 28% and an average temperature of 65ºC. Keywords: dried coconut drier machine, solar energy